The Influence of Agricultural Commodity on F&B Company’s Performance in Indonesia - Rokhim, Rofikoh; Setiawan, Puguh (International Research Journal of Business Studies, 2013)
This research examines the influence of agricultural commodity price movements on stock price and gross profit of food and beveragecompanies in Indonesia, as well as the effect of volatility prices of agricultural commodities. Using time series data of food and beverages (F&B) companies that are listed at the Indonesia Stock Exchange (IDX), this research calculating the event studies to find the abnormal returns. The results showed that the movement of agricultural commodity prices has a positive effect on stock prices of F&B companies, with the dominant influence of commodity prices of corn and sugar. Agricultural commodity prices also affect positively on gross profit F&B companies, with the dominant influence of commodity prices of corn and palm oil. The increase in prices of agricultural commodities simultaneously affect the value of a positive cumulative abnormal return for stocks of F&B companies. The results also showed that the decline of agricultural commodities simultaneously affect the value of negative cumulative abnormal return for stocks of F&B companies.